On triplexer design for next generation Ethernet passive optical network systems. (6th January 2009) - Santos, Joao Miguel; Monteiro, Paulo; Hajduczenia, Marek
The standardisation effort targeting 10 Gbit/s EPON systems, together with the requirement for coexistence with the legacy IEEE 802.3ah compliant equipment, impose a set of very tight requirements in terms of wavelength allocation plan for future EPON systems and significant limitations in terms of triplexer design for optical network unit (ONU) modules, where two wavelength channels (or three, when an analogue video overlay is used on the downstream) must be properly separated with minimum power and quality loss, providing also a high quality transmission window for the upstream 1310 nm signal. In this paper, we look closer at the possible triplexer and filter design for emerging 10 Gbit/s EPON systems in the light of current IEEE 802.av Task Force activities and technical limitations of the wavelength division multiplexing (WDM) filter design process.